"We are fighting for a worthy purpose, and we shall not lay down our arms until that purpose has been fully achieved" - Great Britain. Parliamentary Recruiting Committee (London : Parliamentary Recruiting Committee, 1914)
English World War I recruiting notice. Includes English coat of arms at head of title with initials "G. R." adjacent. Text appears in red and blue, with borders in the same colours surrounding the text. "Poster No. 4" and "H. W. & V., Ld. W.8004. 11/14" appears below the outer border.
Caption title.
Also available online
Keywords: Great Britain. -- Parliamentary Recruiting Committee -- Posters; Great Britain -- Armed Forces -- Recruiting, enlistment, etc. -- World War, 1914-1918 -- Posters; Recruiting and enlistment -- Posters; World War, 1914-1918 -- Posters; Broadsides -- Great Britain; War posters -- Great Britain; Great Britain -- Posters